1967
DOI: 10.1161/01.cir.35.2.250
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Intrarenal Blood Flow in Normal and Hypertensive Man

Abstract: Observations were made on eight normotensive subjects and on 12 patients with essential hypertension to determine whether the intrarenal distribution of blood flow is altered in essential hypertension. Dye-dilution curves were recorded across the renal vascular bed and a set of integral transformations, developed by Gomez, was used to determine distribution of blood flow per unit renal blood volume across the renal vascular bed from dye-dilution curves. Observations also were made on two hypertensives and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1967
1967
2001
2001

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…This is in good agreement with the renal blood volume reported by this laboratory in an earlier study (36.7±10.9 ml) (13,14), using a somewhat different system of collection and calculation. Other investigators (15,16) is not yet clear whether this additional volume is within the vessels or outside of them.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in good agreement with the renal blood volume reported by this laboratory in an earlier study (36.7±10.9 ml) (13,14), using a somewhat different system of collection and calculation. Other investigators (15,16) is not yet clear whether this additional volume is within the vessels or outside of them.…”
Section: Discussionsupporting
confidence: 92%
“…It was therefore necessary to estimate average renal blood flow during intervals approximating the duration of each indicator dilution curve. Accordingly, it was assumed that the fractional recoveries of indocyanine green and tritiated water in the renal venous blood are complete and that the fractional recovery of inulin-carboxyl- 14 C is complete in the renal venous blood and urine. This assumption represents a departure from the calculation previously used, in which it was assumed that flow is constant and fractional recovery is variable (1).…”
Section: (3)mentioning
confidence: 99%
“…Previous studies have reported normal to enhanced renal blood and/or plasma flow in the prehypertensive stage and in borderline hypertension, 2,4,19 -22 whereas in sustained hypertension, the consistently observed pattern of renal hemodynamics is characterized by a decreased renal blood and/or plasma flow and a normal to slightly decreased GFR, resulting in an elevated renal filtration fraction. [23][24][25] Renal hemodynamic changes have been supposed to play an important role in the development of hypertension. Evidence for this hypothesis comes from the observation of an abnormal control of renal circulation in subjects with a positive family history of hypertension in response to mental stress, and Bianchi et al 4 found that normotensive offspring of hypertensive parents were characterized by high renal blood flow (RBF) despite normal cardiac output, suggesting a specific renal vasodilation in the prehypertensive stage.…”
Section: Discussionmentioning
confidence: 99%
“…3 -I0 -" Renal blood flow (RBF) and RPF are reported to vary from decreased flow 3 -9 -"• l2 to normal flow 7 10 -"• l3 and even to increased flow, ' 4 -' 3 according to the definition of the severity of the essential hypertension. There is disagreement regarding a possible correlation between the severity of hypertension as shown by the level of arterial blood pressure and RBF.…”
mentioning
confidence: 99%